Characters in Search of Their Author : The Gifford Lectures, 1999-2000 - McInerny, Ralph, 1929-2010 (Book collections on Project MUSE., 2001)
"Is the conviction that there is a God the default position of the human mind? This is the suggestion of Vatican II's Gaudium et spes, as well as Cardinal Newman and even St. Thomas Aquinas. But however natural it is for human beings to acknowledge their maker, it seems almost as natural to throw up obstacles between man and God. Characters in Search of Their Author, the Gifford Lectures delivered by Ralph McInerny in Glasgow in 1999-2000, is devoted to clearing away some of these impediments, mainly those fashioned by philosophers."--Jacket.